Effect of Litter-Derived Dissolved Organic Carbon Addition on Forest Soil Microbial Community Composition - Wang, Min; Tian, Qiuxiang; Liao, Chang; Zhao, Rudong; Liu, Feng (Frontiers in Soil Science, 2021)
The input of dissolved organic carbon (DOC) into soil affects soil organic carbon mineralization and microbial community composition by changing carbon availability. However, up to now, there is little knowledge about the microbial groups that utilize the added DOC and how the incorporation process may vary over time. In this study, we added 13C-labelled litter-derived DOC (treatment) or pure water (control) to a forest soil from different layers to investigate the effects of DOC addition on soil microbial biomass and community composition in a 180-d laboratory incubation experiment. Soil microbial phospholipid fatty acid (PLFA) were measured to assess changes in the microbial community composition. The 13C incorporation into microbial biomass and PLFAs was analyzed to trace the microbial utilization of litter-derived DOC. Our results indicated that DOC addition increased the biomass of gram-negative bacteria, gram-positive bacteria, fungi, and actinomycetes, but the microbial community composition manifested a similar trend for both treatment and control soils at the end of incubation. Proportions of added DOC in different depths of soil microbial PLFAs had no significant difference. Moreover, 17:0 cy and 15:0 PLFAs which are described as the bacterial biomarkers had a greater amount of 13C incorporation than other PLFAs for the topsoil, which indicated that 13C-labelled litter-derived DOC was more easily assimilated by some specific bacterial community. Soil microbial biomass and the incorporation of 13C into PLFA reached its maximum around 30 days after DOC addition and then rapidly reduced to the level comparable to control. Overall, this study demonstrated that the the incorporation of 13C-labelled litter-derived DOC into PLFA in different depth soil had no significant difference, and the incorporation of 13C by bacteria was higher than other microbial groups.